UGL Students' Perception Of Citizenship And Anti-Corruption Education: Importance And Relevance - Lusi Tutur Mulia (Journal Informatic, Education and Management (JIEM), 2025)
Corruption is an extraordinary crime that requires extra efforts to address. The Corruption Eradication Commission (KPK) is taking extra steps to address corrupt behavior by implementing preventive measures through educational institutions. In universities, the KPK collaborates with relevant stakeholders to implement anti-corruption education for students. This study explores students' initial perceptions of civics and anti-corruption education. A qualitative method using a case study approach was used for this research. The findings indicate that the majority of students view civics and anti-corruption education as crucial and relevant to the current state of the nation.